Recovery in a low secure service. (1st September 2017) - Clarke, Caroline; Sambrook, Suzanne; Lumbard, Darren; Kerr, Kevin; Johnson, George
This empirical paper describes a study that explored the lived experience of 'recovery' for six male patients who were detained in a low secure service. Interpretive phenomenological analysis (IPA) was used to capture the subjective meanings that participants ascribed to this process. Participants also discussed the My Shared Pathway initiative as a helpful format for embedding recovery principles. Five superordinate themes were identified: It's a journey; We're vulnerable in here; Relationships with staff; Loss; and Hope. These findings are consistent with those seen in the forensic recovery literature and suggest that My Shared Pathway helps promote recovery in a number of ways. Clinical implications and suggestions for further research are given.